HOSPITAL UTILIZATION IN MALUKU PROVINCE, INDONESIA - Sahrir Sillehu; Agung Dwi Laksono; Ratna Dwi Wulandari; Abu Khoiri (Universitas Airlangga, 2023)
Introduction: Maluku is a region characterized by an archipelago with approximately 1,340 islands and an area of 712,479.69 km2. Most of the site is water (92.4%), while the land area is only around 7.6%. Aims: This study aimed to analyze the determinant of hospital utilization in Maluku Province, Indonesia. Methods: This cross-sectional study surveyed 788 respondents. The variables examined included hospital utilization, age group, gender, education level, work type, marital status, health insurance, transportation cost, and time travel. The author used binary logistic regression in the final stage. Results: The results show that the 30-39 age group was 2.293 times more likely than the ≥ 50 age group to utilize the hospital (OR 2.293; 95% CI 1.177 – 4.466). Married people were more likely to use the hospital 1.764 times than those with the never-married category (OR 1.764; 95% CI 1.074 – 2.898). Christians were 1.599 times more likely than Muslims to utilize the hospital (OR 1.599; 95% CI 1.146 – 2.231). Conclusion: The study concluded that three variables are determinants of hospital utilization among people in Maluku Province, Indonesia. The three were age group, marital status, and religion. The study's results were significant for local policymakers to provide specific directions to accelerate the increase in hospital utility in Maluku Province in Indonesia.